Standards for variation range of RR-intervals at rest and in orthostasis in training of racing skiers with different types of regulation - Shlyk, N. I. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to identify standards for the variation range of RR-intervals at rest and in orthostasis in training of racing skiers with different types of regulation